How does industrial protection affect the agricultural sector? A quantitative general equilibrium analysis for Peninsular Malaysia - Manfred Wiebelt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
This paper investigates quantitatively the effects of trade policy on agriculture in the empirical context of Peninsular Malaysia using a SAM-based multi-sectoral, general equilibrium model. The focus of the analysis is on the economy-wide implications of changes in tariffs on import-substituting manufacturing activities. In general, the results bear out the expectation that industrial protection distorts incentives favoring manufacturing and nontradable activities over agriculture as a whole. Whereas this result is familiar from other recent studies, the general-equilibrium approach allows many additional disaggregate findings. Industrial protection in Malaysia taxes, e.g., not all agricultural sectors. The rubber sector is discriminated by tariff protection for manufacturing, but the oil palm sector is favored due to strong forward linkages to the protected industries.
Keywords: 330; Protektionismus; Landwirtschaft; Sozialprodukt; Allgemeines Gleichgewicht; Malaya